2017
DOI: 10.1371/journal.pone.0185443
|View full text |Cite|
|
Sign up to set email alerts
|

Cortical movement of Bicoid in early Drosophila embryos is actin- and microtubule-dependent and disagrees with the SDD diffusion model

Abstract: The Bicoid (Bcd) protein gradient in Drosophila serves as a paradigm for gradient formation in textbooks. The SDD model (synthesis, diffusion, degradation) was proposed to explain the formation of the gradient. The SDD model states that the bcd mRNA is located at the anterior pole of the embryo at all times and serves a source for translation of the Bicoid protein, coupled with diffusion and uniform degradation throughout the embryo. Recently, the ARTS model (active RNA transport, synthesis) challenged the SDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(63 citation statements)
references
References 52 publications
5
56
0
Order By: Relevance
“…The sensory role of the primary cilium is highly specialized depending upon the tissue or organ system it is localized in. Well-known examples of their specialized roles include mechanosensitive cilia found in blood vessels, kidney, and bone; chemosensitive cilia in the nose; and recently, new evidence has suggested an electrosensitive role of primary cilia in the nervous system [ 21 , 22 , 23 ]. To effectively translate such a diverse range of extracellular signals, ciliary protein and receptor composition, as well as cilia structure, all come together to contribute to context-appropriate signaling [ 24 ].…”
Section: Calcium and Ciliary Signal Transduction: Sensory Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensory role of the primary cilium is highly specialized depending upon the tissue or organ system it is localized in. Well-known examples of their specialized roles include mechanosensitive cilia found in blood vessels, kidney, and bone; chemosensitive cilia in the nose; and recently, new evidence has suggested an electrosensitive role of primary cilia in the nervous system [ 21 , 22 , 23 ]. To effectively translate such a diverse range of extracellular signals, ciliary protein and receptor composition, as well as cilia structure, all come together to contribute to context-appropriate signaling [ 24 ].…”
Section: Calcium and Ciliary Signal Transduction: Sensory Functionmentioning
confidence: 99%
“…This could be explained by either cytoplasmic Ca 2+ being needed to precede cilia sensory function, enabling the cilia to sense the electrical stimuli, or a separate Ca 2+ microdomain forming in the cilia that is distinct from cytosolic Ca 2+ . Together, this suggests that primary cilia have a critical role in translating Ca 2+ -induced cellular responses into electrical stimulation [ 21 ].…”
Section: Calcium and Ciliary Signal Transduction: Sensory Functionmentioning
confidence: 99%
“…To precisely monitor the path of Bcd movement during early development, a sensitive approach was developed that allowed for the study of the spatial Bcd movement during the early nuclear cycles using single confocal sections [ 20 ]. This study revealed, for the first time, that Bcd moved at the cortex of the egg but never entered the inner portion filled with yolk (Fig.…”
Section: History Of Mechanisms To Explain the Occurrence Of The Bicoimentioning
confidence: 99%
“…During this sleeping phase, Bcd still moved slowly at the cortex to the posterior. Again, the speed and location of Bcd movement was not compatible with the diffusion properties claimed by the SDD model [ 20 ], nor with that from the nucleocytoplasmic shuttle model [ 22 ]. Notably, the inner part of the egg, i. e. the yolk still acted as a non-permissive territory (Fig.…”
Section: History Of Mechanisms To Explain the Occurrence Of The Bicoimentioning
confidence: 99%
See 1 more Smart Citation